Processadores para laticínios e correlatos destinados a agroindustria familiar: Aspectos relativos a energia - Pavani, Sergio Adalberto (2006)
The familiar agroindustry is an option to increase income and employment in the countryside due to the requirement of low investments, low concentration of inputs, low energy consumption and pollution creation. Besides, it can use local availability and diversify the production by occupying niches of special markets such as organic food, natural food or specialties. When the agricultural entrepreneurs implant their industries, they suffer due to the lack of appropriate orientation to elaborate their projects and to specify processing equipments among others. This study aims at demonstrating the necessity to invest in aspects related to energy and project in the dairy products processing as well as the importance of this sector development to the growth of non-agricultural rural employment in Brazil.